THE INFLUENCE MECHANİSMS OF AUTOMOTİVE SECTOR ON TURKİSH ECONOMY İN MACROECONOMİC MANNER AND A SECTOR ANALYSİS (Third Sector Social Economic Review, 2020)
Turkish automotive industry exports to more than 150 countries and holds great importance for Turkey. The aims of this research are; to reveal the macroeconomic contributions of Turkish automotive industry, to identify strengths and weaknesses of the sector using SWOT analysis and to make suggestions to increase contributions to Turkish economy. In this regard, contributions of the industry in the areas such as employment, growth, balance of payment, exportation, tax revenues, and foreign direct investment are presented. Also, a SWOT analysis has been performed to determine strengths and weaknesses of the sector. It is concluded that strengths of the sector concentrate on manufacture-related topics, whereas weaknesses might appear, especially, on importation and demand-related topics. According to the results of SWOT analysis, suggestions have been made in four different strategies. Implementations of the suggestions developed within the scope of these strategies are of great importance for development and increasing the contribution of the sector to Turkish economy.
Keywords: Automotive sector; Makroeconomic Effect; SWOT Analysis